Seed priming with sodium nitroprusside attenuates the effects of water deficit on soybean seedlings - Gavassi, Marina Alves; Gaion, Lucas Aparecido; Monteiro, Carolina Cristina; Santos, Joel Cabral; Carvalho, Rogério Falleiros (Comunicata Scientiae, 2019)
Considering that water deficit is one of the main environmental factors responsible for low soybean yield and that nitric oxide (NO) has been shown to be a fundamental part of plant defense signaling during stress, the aim of the present study was to evaluate the effect of seed priming with nitric oxide on the induction of water deficit tolerance during the initial development of soybean. Thus, seeds were treated with 0 (water only), 50, 100 or 250 μmol.L-1 sodium nitroprusside for 6 hours. Additionally, untreated seeds were used. After drying, the seeds were placed in containers filled with a commercial substrate mixture and vermiculite and irrigated to 100% and 50% field capacity. Biometric and biochemical evaluations (pigment and proline contents) were performed after 14 days. It was concluded that pretreatment of soybean seeds with 50 to 250 μmol.L-1 SNP attenuated the effects of water deficit on stem growth, leaf area, and shoot dry matter and induced carotenoid biosynthesis. The accumulation of proline in the leaves was pronounced in the treatments with 100 and 250 μmol.L-1 SNP, while 100 μmol.L-1 SNP induced proline accumulation in the roots.